2013
DOI: 10.4172/2161-0509.s12-002
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and its Correlates among Rural Primary School Children of Fogera District, Northwest Ethiopia

Abstract: Background: Malnutrition is a major public health concern affecting a significant number of school children influencing their health, growth and development, and school academic performance.Objective: To determine the nutritional status of school children in terms of stunting, underweight and thinness and to identify its correlates at Fogera woreda, Northwest Ethiopia, 2012.Methods: Institutional and community based cross sectional study was conducted from June to December, 2012. The study included 790 primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
37
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 18 publications
24
37
6
Order By: Relevance
“…With this regards, children living in a family of five or more were more stunted than their counterparts. The finding corroborates previous studies in Sudan [44], Pakistan [45], Ethiopia [43] and elsewhere [46]. Logically, as family size increases, the chance of becoming malnourished also increase probably due to other factors that may contribute to nutritional status, such as income of the family become less when there is increased family size.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With this regards, children living in a family of five or more were more stunted than their counterparts. The finding corroborates previous studies in Sudan [44], Pakistan [45], Ethiopia [43] and elsewhere [46]. Logically, as family size increases, the chance of becoming malnourished also increase probably due to other factors that may contribute to nutritional status, such as income of the family become less when there is increased family size.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, undernourished children from rural Bangladesh [16] and Northwest Ethiopia were less likely to have received vaccination [43]. Non-immunized children are more likely to be frequently infected with vaccine preventable diseases such as diarrhea and respiratory infections, which are known in depleting nutrients from the body.…”
Section: Discussionmentioning
confidence: 99%
“…This result could be due to lack of education of the students' parents as less than half of them were illiterate or read and writeand this lead to lack of knowledge and awareness about parasitic infection among parents and their children. The present result is in accordance with Zakai (2007) (46) , who reported that about two thirds of the studied subject had a below average degree of awareness about parasites and parasitic diseases.Nutrition has become very important in both preventive and curative health care 47) . Concerning the distribution of studied students according to their total Mini Nutritional Assessment Scale (MNAS) score,about two thirds (66.7%, 62.3%) of students infected by one parasite and those infected by two parasites were mal nourished respectively (table 8).…”
Section: Discussionmentioning
confidence: 99%
“…Nairobi, Kenya and 30.7% (Mekonnen, Tadesse, & Kisi, 2013) in Northwest of Ethiopia among school-age children. The differences observed between children from Kenya (Chesire et al, 2008) and present study may be attributed to regional differences: participants in the current study were from semi-rural setting; whereas in the Kenyan study was conducted in peri-urban area.…”
Section: Normal Deficit Overmentioning
confidence: 99%